PENGARUH PENDIDIKAN KESEHATAN TENTANG PERAWATAN BAYI BARU LAHIR TERHADAP PENGETAHUAN IBU DALAM MENCEGAH HIPERBILIRUBINEMIA NEONATUS : Literature Review - Leily Muhafilah (2020)
Neonatal hyperbilirubinemia is accumulation of unconjugated bilirubin in the circulation (more than 10 mg / dl) that can occur after 24 hours of birth, if the levels reach 5-7 mg / dL and can have an impact on infant mortality if handling is poor. However, maternal knowledge about hyperbilirubinemia is still low. So we need a method to increase maternal knowledge about hyperbilirubinemia. Health education with the media methods used. The purpose of the literature review research is to analyze the literature relating to health education of maternal knowledge in preventing the occurrence of neonatal hyperbilirubinemia. This literature review uses a database through Google Scholar, Pubmed, Elsevier, Paediatrica Indonesiana, and Doaj in the last 5 years. Only 5 journals have been screened in accordance with the predetermined inclusion criteria. The effect of health education on postpartum mothers is very influential in preventing neonatal hyperbilirubinemia in newborns, as well as the media used in health education. All literature studies that have been found still need to be developed and reexamined, so that for further development and research in order to get better results than before.